Considerations about the delimitation between the concepts of author and participant: past, present and future (2018)
As an amplifying device of the criminal act, the participation is a mechanism to impose the penal sanction, keeping the principle of legality, the principle of the act and, at the time, avoiding impunity. Its study was subject to the interpretative extens